Preclinical insights into gamma-tACS: foundations for clinical translation in neurodegenerative diseases - Sánchez-Garrido Campos, Guillermo; Zafra, Ángela M.; Estévez-Rodríguez, Marta; Cordones, Isabel; Ruffini, Giulio; Márquez-Ruiz, Javier (Frontiers in Neuroscience, 2025)
Gamma transcranial alternating current stimulation (gamma-tACS) represents a novel neuromodulation technique with promising therapeutic applications across neurodegenerative diseases. This mini-review consolidates recent preclinical and clinical findings, examining the mechanisms by which gamma-tACS influences neural oscillations, enhances synaptic plasticity, and modulates neuroimmune responses. Preclinical studies have demonstrated the capacity of gamma-tACS to synchronize neuronal firing, support long-term neuroplasticity, and reduce markers of neuroinflammation, suggesting its potential to counteract neurodegenerative processes. Early clinical studies indicate that gamma-tACS may improve cognitive functions and network connectivity, underscoring its ability to restore disrupted oscillatory patterns central to cognitive performance. Given the intricate and multifactorial nature of gamma oscillations, the development of tailored, optimized tACS protocols informed by extensive animal research is crucial. Overall, gamma-tACS presents a promising avenue for advancing treatments that support cognitive resilience in a range of neurodegenerative conditions.